Working in the Context of Austerity - Baines, Donna; Cunningham, Ian (Bristol University Press, 2020)
Available Open Access under CC-BY-NC-ND licence. How to do more with less? This is, essentially, austerity's onerous question. Its default answer, in turn, has been to defer, download and outsource the burden of being overtasked and cash strapped.